Electron microscopy study of the central retinal fovea in Pied flycatcher: evidence of a mechanism of light energy transmission through the retina. Issue 6 (June 2020) - Zueva, Lidia; Golubeva, Tatiana; Korneeva, Elena; Resto, Oscar; Inyushin, Mikhail; Khmelinskii, Igor; Makarov, Vladimir
Abstract: We present unique ultrastructural data on avian retinal cells. Presently and earlier (Zueva et al., 2016) we explored distribution of intermediate filaments (IFs) in retinal cells of the Pied flycatcher ( Ficedula hypoleuca, Passeriformes, Aves) in the central foveolar zone. This retinal zone only contains single and double cone photoreceptors. Previously we found that continuous IFs span Müller cells (MC) lengthwise from the retinal inner limiting membrane (ILM) layer up to the outer limiting membrane (OLM) layer. Here we describe long cylindrical bundles of IFs (IFBs) inside the cone inner segments (CIS) adjoining the cone plasma membrane, with these IFBs following along the cone lengthwise, and surrounding the cone at equal spacing one from the other. Double cones form a combined unit, wherein they are separated by their respective plasma membranes. Double cones thus have a common external ring of IFBs, surrounding both cone components. In the layer of cilia, the IFBs that continue into the cone outer segment (COS) follow on to the cone apical tip along the direction of incident light, with single IFs separating from the IFB, touching, and sometimes passing in-between the light-sensitive lamellae of the COS. These new data support our previous hypothesis on the quantum mechanism of light energy propagation through the vertebrate retina (Zueva et al., 2016, 2019). Abstract : Biological sciences; Cell biology; Cytoskeleton; Developmental biology; TEM; Passeriformes; Inverted bird retina; Central fovea; Müller cell's intermediate filaments; Cone's intermediate filament bundles; Intermediate filament distribution